THE SOCIAL RESPONSABILITY OF THE COMPANIES - Rozas Flores, Alan Errol (2009)
The public wants to know more on the companies and not of casual way but systematic to take better decisions of investment and of saving (felicitous balance between the benefits and the risks) and to evaluate the sustainable of the company with rules concrete on his legitimacy to operate: his conduct to do businesses and his equilibrium balanced of economic subjects, social and environmental. There is an intimate relation between what the development sustainable and the Social Responsibility of the Company (RSE). The companies declare a commitment with the development sustainable, because they understand that it has to see with his feasibility. And in this, coexist two big motivations; imperative ethical and also imperative of businesses. In relation with the first, ascertains the conviction that the companies are responsible by his impact in the society and that distinct groups of interest (stakeholders), not only the investors, have right to knowledge. In relation with the second, also exists the conviction that the companies that are more open will win confidence of his groups of interest, will develop a better reputation, will have more allies and least problems, and like this will be perceived and administering better all his risks; In other words it will show good management that sees further of the short term. The moves to the company is the best form to do businesses, the one who ensure this permanence in the time. And this itself conciliates with the imperative ethical of many: the care and the responsible action of the means environment, the transparency of information, the good business government, the promotion of practices of healthy businesses, respect to the members of the chain of value, the attention and care or consideration to the people of the companies in social appearances, of health, of security.